Modelo numérico eficiente para flujo electrocinético en sistemas microfluídicos con geometrias complejas - Kler, Pablo Alejandro (2007)
Microfluidic devices like those used in chemical and biomedical applications basically consist of different networks of microchannels that interconnect chambers and reservoirs. The transport of fluids throughout the network is driven by pressure gradients, electric fields, or a combination of the two, which yields to the so-called electrokinetic flow. Analytical and numerical models have been used to aid in the design and simulation before fabrication with MEMS technology. Efficient numerical models are required since typical microchannel dimensions are in the range of several micrometers in width and depth and some centimeters in length. The numerical solution is carried out by using PETSC-FEM, for which we have developed a python interface for pre- and postprocessing using third-parties programs (Tetgen, Mayavi). A parallelizable preconditioner for Domain Decomposition Methods (DDM) by means of Finite Element discretization of Navier-Stokes equations is used to improve the convergence of problems with different scales like in microfluidic problems.